ORGANIZATIONAL ACTIVITY OF THE DEPARTMENT OF PHYSICS, MATHEMATICS AND TECHNICAL SCIENCES OF THE UZBEKISTAN ACADEMY OF SCIENCES - Ismailov Alisher (Galaxy International Interdisciplinary Research Journal, 2022)
This article describes the organizational activities of the Department of Physical, Mathematical and Technical Sciences of the Academy of Sciences of the Republic of Uzbekistan. The organization of department-based scientific institutions, their inclusion in the Academy of Sciences, their transfer to another system, their termination, and their reorganization have been analyzed. As a result of the analysis, the institutions of the Department that were part of the academy, transferred to another system, terminated and reorganized were identified.